2019
DOI: 10.5937/ejae16-21569
|View full text |Cite
|
Sign up to set email alerts
|

Causes of failure of the Phillips curve: Does tranquillity of economic environment matter?

Abstract: Although empirical literature regarding the Phillips curve is sizeable enough, there is still no wide consensus on its validity and stability. The literature shows that the Phillips relationship is fragile and varies across countries and time periods; a statistical relationship that appears strong during one decade (country) may be weak the next (other). This variability might have some grounds for idiosyncrasy of a country and its economic environment. To address it, this paper scrutinizes the Phillips relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
(26 reference statements)
2
4
0
Order By: Relevance
“…Based on the results of this research, we find that the dynamics of both backward-looking and forward-looking specifications of the Phillips Curve change during recessionary periods and the empirical relationship is no longer valid. This result is in line with the findings of Mazumder (2018), Ball and Mazumder (2019) and Sovbetov and Kaplan (2019b).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Based on the results of this research, we find that the dynamics of both backward-looking and forward-looking specifications of the Phillips Curve change during recessionary periods and the empirical relationship is no longer valid. This result is in line with the findings of Mazumder (2018), Ball and Mazumder (2019) and Sovbetov and Kaplan (2019b).…”
Section: Discussionsupporting
confidence: 92%
“…He states that the relationship is often evasive or absent in less-developed economies. Similar conclusions were made by Sovbetov and Kaplan (2019b) who have studied the Phillips curve in 41 different countries during tranquil and recessionary periods. They note that the Phillips curve might not work as notionally in lessdeveloped or crisis-prone countries due to a lack of well-established and freely operating structure of macroeconomic foundations and motivations.…”
Section: Literature Reviewsupporting
confidence: 82%
“…Once the unemployment rate exceeds 6.54%, there is no correlation between inflation and unemployment rate. Sovbetov & Kaplan (2019) researched the existence of the Phillips curve in 41 countries for period 1980-2016, and they have confirmed that relationship between these two variables differs over time: the Phillips curve is more present in developed countries than in emerging countries; but the Phillips curve relationship is not applicable during periods of recession, even for developed countries.…”
Section: O N L I N E F I R S Tmentioning
confidence: 90%
“…Even though it has been researched many times, the Phillips curve is not applicable to all countries and all time periods. Statistical relationship that appears strong during one decade or country, may be weak during the next one or in another country (Sovbetov & Kaplan, 2019). Bulligan & Viviano (2017) presented correlation between unemployment rate and annual nominal wage growth in the euro area in the period Q1 1999-Q4 2015.…”
Section: O N L I N E F I R S Tmentioning
confidence: 98%
“…Knežević and Dobromirov (2016) show that different factors specific to a particular market have a significantly greater impact on the economy than macroeconomic indicators. Sovbetov and Kaplan (2019) show that tranquility of economic environment is significantly important for the development. A good way to look at the development and democracy of a society is to observe the orderliness of the financial market.…”
Section: Introductionmentioning
confidence: 99%